IMPLEMENTASI WAKAF TUNAI DI MASJID DARUSH SHOLIKHIN KOTA BATU - Puspita, Ira Chandra (Fakultas Syariah, 2012)
This writing aims at identifying problems that emerged in cash waqaf in Darush Sholikhin Mosque Batu and to understand about cash waqf mechanism and its adjustments according to the Indonesian law. Nadzir of Darush Sholikhin Mosque applied effectiveness approach in using cash waqf result, namely waqaf fund. This waqf was directly used to build the Mosque. The implementation of cash waqaf in Darush Sholikhin is a form of traditional waqf which is not accommodated in UUW and PP Number 42, 2006 regulating cash waqaf implementation as investment that must be implemented through Shari’ah Financial Institutions (LKS) pointed by Minister. Although the base of its implementation still refers to cash waqaf books issued by Division of Waqaf, Department of Religious Affairs of Indonesia, its implementation has not fulfilled the requirements as stated in cash waqf regulation. Nonetheless, it is implementation is appropriate with fiqh wakaf that is lawful in Islamic perspective. Tulisan ini bertujuan untuk mengidentifikasi masalah yang muncul pada wakaf tunai di Masjid Darush Sholikhin Batu dan memahami mekanisme wakaf tunai berikut kesesuaiannya dengan peraturan perundangan yang berlaku di Indonesia. Nadzir masjid Darush Sholikhin menerapkan pendekatan efektifitas pemanfaatan hasil dari wakaf tunai. Dana wakaf yang diterima diwujudkan secara langsung dalam pembangunan masjid tersebut. Pelaksanaan wakaf tunai di Darush Sholikhin merupakan pelaksanaan wakaf tradisional yang tidak terakomodir oleh UUW dan PP No. 42 tahun 2006, yang mengatur mengenai pelaksanaan wakaf tunai sebagai investasi yang harus dilakukan melalui LKS yang ditunjuk oleh menteri. Meskipun dasar pelaksanaannya masih berpedoman pada buku-buku tentang wakaf tunai yang dikeluarkan oleh Direktorat Pemberdayaan Wakaf, Departemen Agama Republik Indonesia, pelaksanaannya tidak memenuhi ketentuan dalam perundang-undangan tentang pelaksanaan wakaf tunai. Akan tetapi, pelaksanaannya sesuai dengan ketentuan Fiqh wakaf sehingga sah hukumnya dalam perspektif Islam.